2023
DOI: 10.1038/s41598-023-32505-8
|View full text |Cite
|
Sign up to set email alerts
|

Grazing-incidence diffraction reveals cellulose and pectin organization in hydrated plant primary cell wall

Abstract: The primary cell wall is highly hydrated in its native state, yet many structural studies have been conducted on dried samples. Here, we use grazing-incidence wide-angle X-ray scattering (GIWAXS) with a humidity chamber, which enhances scattering and the signal-to-noise ratio while keeping outer onion epidermal peels hydrated, to examine cell wall properties. GIWAXS of hydrated and dried onion reveals that the cellulose ($$110/1\overline{1}0$$ 110 / … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…We speculate that the 7.4 nm distance would not be very different in the hydrated state as we have previously reported that pectin spacings along the plane of the cell wall do not collapse after drying in the onion cell wall. [ 30 ] Pectin has a persistence length on the scale of 10 nm, [ 31 ] so it is likely to have a stiff conformation. Along with CMFs, pectin is also known to reorient towards the stretch direction.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the 7.4 nm distance would not be very different in the hydrated state as we have previously reported that pectin spacings along the plane of the cell wall do not collapse after drying in the onion cell wall. [ 30 ] Pectin has a persistence length on the scale of 10 nm, [ 31 ] so it is likely to have a stiff conformation. Along with CMFs, pectin is also known to reorient towards the stretch direction.…”
Section: Discussionmentioning
confidence: 99%
“…nanocellulosic materials due to its crystalline nature [73]. The additional diffraction peaks observed throughout the 90° 2θ range indicate the presence of other crystalline constituents such as silica, a known component of rice straw.…”
Section: Characterisation Of Cellulose Fibresmentioning
confidence: 98%
“…00-050-2241). Cellulose Iβ is the most dominant allomorph in higher plants and is frequently targeted for the production of high-quality nanocellulosic materials due to its crystalline nature [73]. The additional diffraction peaks observed throughout the 90 • 2θ range indicate the presence of other crystalline constituents such as silica, a known component of rice straw.…”
Section: Characterisation Of Cellulose Fibresmentioning
confidence: 99%
“…The CI of the MFC and MFC/clay films slightly increased after heat treatment, presumably owing to the increase of the cellulose crystallites size. This was checked using the Debye-Scherrer equation [46]:…”
Section: Structure and Morphology Analysis Of Mfc-clay Composite Filmsmentioning
confidence: 99%